Effect of PCC on Thrombin Generation among Patients on Factor Xa Inhibitors with Major Bleeding or Needing Urgent Surgery (GAUGE): Design and Rationale - Shaw, Joseph R.; Unachukwu, Ubabuko; Cyr, Joseph; Siegal, Deborah M.; Castellucci, Lana A.; Dreden, Patrick Van; Dowlatshahi, Dar; Buyukdere, Hakan; Ramsay, Timothy; Carrier, Marc (TH Open, 2023)
Background Direct factor Xa inhibitors (FXaIs) account for most oral anticoagulant use and FXaI-associated bleeding events are common. Clinicians have variable national and regional access to specific FXaI reversal agents such as andexanet alfa. Many centers have adopted the use of prothrombin complex concentrates (PCCs) as hemostatic therapy for FXaI-associated major bleeding events. PCC does not impact circulating FXaI levels and its mechanism of action to achieve hemostasis in FXaI-associated bleeding is uncertain. While PCC increases quantitative thrombin generation assay (TGA) parameters, it does not correct FXaI-altered thrombin generation kinetics, nor does it normalize thrombin generation. Clinical data supporting the use of PCC are based on cohort studies reporting clinical hemostatic efficacy, which is difficult to measure. The benefits of PCC for FXaI-associated bleeding beyond supportive care are uncertain.Objective GAUGE is a prospective observational study designed to measure the effects of four-factor PCC administration (Octaplex) on TGA parameters among patients with FXaI-associated bleeding or needing urgent surgery.Methods Laboratory outcomes will include the mean paired change in TGA parameters from pre- to post-PCC administration and the proportion of participants whose post-PCC TGA values fall within a defined reference range. Clinical outcomes will include hemostatic efficacy, thromboembolic complications, and all-cause death at 30 days post-PCC.Conclusion Development of a viable and universally accessible FXaI bleed management strategy is crucial. GAUGE will provide in vivo data on the effects of PCC among patients with FXaI-associated bleeding.
Keywords: hemostasis; factor Xa inhibitors; dabigatran; anticoagulation reversal